Electronic Structure, Thermodynamics functions and Physical properties and charges study for derivatives ring 4-(1,3,4-thiadiazol-2- yl)benzene-1,3-diols by using Ab Intio calculations(RHF Method) - A. Mohammad, Manal; A. Gawad, Shatha (Al-Qadisiyah Journal of Pure Science, 2018)
This study involved the adoption of the program (Gaussian 03) to use the method of calculation the total (Ab initio of method) according to the Hartree – Fock method (RHF) , for the purpose of the expense of dimensional geometric ( lengths and angles bond) when the geometry of a balanced, functions thermodynamic, some physical properties, charges for derivatives ring 4- (1,3,4-thiadiazol-2-yl)benzene-1,3-diols. Calculation results have shown that the compound (R-NHC6H5)has highest value of thermodynamic functions (E0 , H0 , G0 , A0) but the compound (R-NHC6H4-Cl) has the highest value of heat capacity and Entropy (CV , CP ,S0) . The results showed that both nitrogen atoms (N9 , N8 ) has the highest negative charge when the compound (R-NH2) , which makes it a strong legend when Linked to metal and the formation of the complex. For (R-NH2 , R-NHC6H5 , R-NHC6H4-Cl , R-NHC6H4-F) molecules the calculated some of physical properties ( dipole moment μ in Debye ) , orbital energies (EHOMO , ELUMO in e V ), IP (in e V) , (measurement stability Δ ) , hardness ɳ and Electron Affinity EA ).Also For these molecules the calculated (ΔHf 0 (in kJ/mole) by using (semi-empirical method AM1 model in MOPAC program). Calculation results have shown that the compound (R-NHC6H4-F) the lower value of the heat of formation (the more Stability) as well as has less value of IP that means it’s the highest active between the compounds. When the compound (R-NH2) has less value of orbital energies (EHOMO , ELUMO) and ΔE that means this compound more active than other compounds ,This difference in results come according to the difference of substituted groups.